(untitled) (Global Journal of Human-Social Science, 2023)
A man s shirt made during the mid 1950 s whose evidence of having existed is a family portrait is the trigger in this very article of observations about the ingeniosity surrounding the daily and domestic production of those objects that result from and on the materiality of the common person history and therefore in the idea of the construction of thought in Design